The Importance of Training in Human Resource Development within Clusters in The North-West Region of Romania - Alina Natalia POP (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2021)
This paper presents research on the importance of training in human resource development within clusters in the North-West Region of Romania. Data on the analysis of the importance of training as an element of human resource and cluster performance were collected during the years of doctoral research. The processing, analysis of the obtained data and interpretation of the research results were performed with the help of SPSS 20.00 program to determine the key factors leading to human resource development and efficiency within the clusters. This paper highlights that complex process at the level of clusters through the degree of technology, management values, the importance of competitive advantage over training, the degree of investment in training. This study brings to the fore the development capacity of the individual, organizational development, increasing the degree of involvement, improving performance, meeting the current and future needs of clusters in the field of human resources. Such research is extremely useful at national and international level in order to facilitate the training of as many employees of organizations as possible.